New Consumer Products Branding, Packaging and Labeling in Nepal - Sharma, Bed Nath (Journal of Nepalese Business Studies, 2009)
This paper focuses on existing practice of branding, packaging and labeling of new products in consumer product manufacturing units. Product identification is not possible without brand name. Protection of product is also equally important to provide quality product for consumer satisfaction. Information regarding the product such as: ingredents, guidelines to use, price, produced and expiry date etc. are also concerned subject of the potential buyer. All these aspects have to be considered for effective promotion of product. It is useful for immediate introduction and recovery in the market by a new product. Key words: Product identification, promotion, protection, information, consumer satisfaction The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page: 16-24